Peran Nutrisi Dalam Meningkatkan Kinerja Atlet - Nimrot Manalu; Miftahul Ihsan; Jhon Paskah; Dian Rizky; Purnama Tarigan; Rikky Junus Manalu; Aria Fernando; Muhammad Rifki; Andes Martua (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Optimal nutrition plays an important role in increasing endurance, strength, and accelerating the recovery process for athletes. This study aims to evaluate the impact of macronutrient (carbohydrate, protein, and fat) and micronutrient (vitamin and mineral) consumption on athletes' physical performance. This study used an experimental method involving 30 athletes who were divided into two groups: one group with a diet that had been adjusted to sports needs and the other group who underwent a diet without strict supervision. The results showed that the group with a balanced diet experienced a 15% increase in endurance, 10% increase in muscle strength, and faster recovery compared to the control group. These results confirm that the right nutritional consumption pattern can improve performance and accelerate post-workout recovery.